Developing Gen Z's Psychological Resilience: The Role of Psychological Capital, Job Demand and Perceived Organizational Support - Putra, Yanuar Surya; Utomo, Hardi; Purwanti, Endang (Faculty of Economics, Universitas Sriwijaya, 2024)
This studyis to examine and clarify the impact of psychological capital and job demands on psychological resilience using perceived organizational support as a mediator. The participants are Gen Z employees who work within the business sectors in Salatiga and the sample size was determined using the Slovin formula, resulting in a total of 245 respondents. The statistical tool used in this research is path analysis with Partial Least Square. This study concludes that psychological capital and job demands have a significant effect on the Gen Z employees’ psychological resilience in Salatiga and perceived organizational support is a full mediating variable. Through perceived organizational support Gen Z employees who feel supported by their organization are more likely to leverage their psychological resources effectively, leading to greater resilience in the face of challenges, and organizations can help Gen Z employees navigate job demands more effectively and foster greater psychological resilience.